Aberrant Regulation of Messenger RNA 3′-Untranslated Region in Human Cancer - Isabel López de Silanes; María Paz Quesada; Manel Esteller (Cellular Oncology)
The messenger RNA 3′-untranslated region (3′UTR) is emerging as critically important in regulating gene expression at posttranscriptional levels. The 3′UTR governs gene expression via orchestrated interactions between mRNA structural components (cis-elements) and specific trans-acting factors (RNA-binding proteins and non-coding RNAs). Alterations in any of these components can lead to disease. Here, we review the mutations in 3′UTR regulatory sequences as well as the aberrant levels, subcellular localization, and posttranslational modifications of trans-acting factors that can promote or enhance the malignant phenotype of cancer cells. A thorough understanding of these alterations and their impact upon 3′UTR-directed posttranscriptional gene regulation will uncover promising new targets for therapeutic intervention.